The addition of methanol to Criegee intermediates. Issue 32 (1st August 2019) - Aroeira, Gustavo J. R.; Abbott, Adam S.; Elliott, Sarah N.; Turney, Justin M.; Schaefer, Henry F.
Abstract : High level ab initio methods are employed to study the addition of methanol to the simplest Criegee intermediates and its methylated analogue. Kinetic rate constants over a range of temperatures are computed and compared to experimental results. Abstract : Bimolecular reactions involving stabilized Criegee intermediates (SCI) have been the target of many studies due to the role these molecules play in atmospheric chemistry. Recently, kinetic rates for the addition reaction of the simplest SCI (formaldehyde oxide) and its methylated analogue (acetone oxide) with methanol were reported both experimentally and theoretically. We re-examine the energy profile of these reactions by employing rigorous ab initio methods. Optimized CCSD(T)/ANO1 geometries are reported for the stationary points along the reaction path. Energies are obtained at the CCSD(T)/CBS level of theory. Contributions of full triple and quadruple excitations are computed to assess the convergence of this method. Rate constants are obtained using conventional canonical transition state theory under the rigid rotor harmonic oscillator approximation and with the inclusion of a one-dimensional hindered rotor treatment. These corrections for internal rotations have a significant impact on computed kinetic rate constants. With this approach, we compute rate constants for the addition of methanol to formaldehyde oxide (H2 COO) and acetone oxide [(CH3 )2 COO] at 298.15 K as (1.2 ± 0.8) × 10 −13 and (2.8 ± 1.3) × 10 −15 cm 3 s −1, respectively. Additionally, we investigate the temperature dependence of the rate constant, concluding that the transition state barrier height and tunneling contributions shape the qualitative behaviour of these reactions.